2012
DOI: 10.33584/jnzg.2012.74.2873
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Plantain (Plantago lanceolata L.) responses to defoliation in Uruguay

Abstract: This trial provided information about the effects of defoliation intensity and frequency on the productivity and plant population of a plantain pasture. Despite the restrictions in plantain management, the focus is to promote its use as specialised pasture for specific purposes. Maximum herbage production was 10.9 t DM/ha/year for a frequent and severely defoliation treatment. Frequency of defoliation affected productivity at different times, mainly in spring (P=0.0013), production being promoted by frequent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This effect has been previously observed by Cranston et al (2015b), where the proportion of plantain increased as the proportion of chicory in the sward declined. Similarly, Ayala et al (2011a) and Ayala et al (2011b) have observed natural reseeding in plantain swards and suggested that the process acts as a mechanism to maintain plant density. This degree of success has rarely been observed in other pasture species, particularly in New Zealand grazing systems.…”
Section: Paddockmentioning
confidence: 93%
“…This effect has been previously observed by Cranston et al (2015b), where the proportion of plantain increased as the proportion of chicory in the sward declined. Similarly, Ayala et al (2011a) and Ayala et al (2011b) have observed natural reseeding in plantain swards and suggested that the process acts as a mechanism to maintain plant density. This degree of success has rarely been observed in other pasture species, particularly in New Zealand grazing systems.…”
Section: Paddockmentioning
confidence: 93%